2012
DOI: 10.1111/j.1747-4477.2012.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smear layer removal by bicarbonate soda, ethylenediamine tetraacetic acid with cetrimide and sodium hypochlorite with a new model

Abstract: Various methods are used to evaluate irrigants. The primary aim was to develop a model for preliminary testing of potential irrigants. The second aim was to investigate the effect of bicarbonate soda on smear layer by comparing it with ethylenediamine tetraacetic acid with cetrimide (EDTAC) and sodium hypochlorite (NaOCl). Extracted human single-canal teeth were halved, and a uniform filing method was used to create smear layer. The following solutions were then applied - distilled water (control), 1% NaOCl, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Many products contain cetrimide because its addition improves the efficacy of irrigating solutions and is reported to have bactericidal and fungicidal properties. [ 12 17 ] In this SEM study, the main goal was to evaluate the effectiveness of 5.25% NaOCl with final rinse of 17% EDTA and Savlon™ irrigation solution used with EndoVac and EndoActivator for removing CH from the root canal walls. The results revealed that none of the methods used were efficient in removing the entire CH from the walls.…”
Section: Discussionmentioning
confidence: 99%
“…Many products contain cetrimide because its addition improves the efficacy of irrigating solutions and is reported to have bactericidal and fungicidal properties. [ 12 17 ] In this SEM study, the main goal was to evaluate the effectiveness of 5.25% NaOCl with final rinse of 17% EDTA and Savlon™ irrigation solution used with EndoVac and EndoActivator for removing CH from the root canal walls. The results revealed that none of the methods used were efficient in removing the entire CH from the walls.…”
Section: Discussionmentioning
confidence: 99%
“…Many products contain cetrimide, because its addiction improves efficacy of irrigating solutions: cationic surfactants have been reported to have bactericidal and fungicidal properties. 17,18 Many studies reported the ability of chelating solutions to reduce or eliminate the smear layer, but no reports evaluated concentration of calcium ions removed from teeth with different chelators. 19 Accordingly, the objective of the present study was to evaluate and compare the influence of cetrimide on decalcifying capability of different irrigating solutions.…”
Section: Introductionmentioning
confidence: 99%